Rhinology future trends: 2017 EUFOREA debate on allergic rhinitis - Scadding, Glenis; Bousquet, Jean; Bachert, Claus; Fokkens, Wytske; Hellings, Peter W.; Prokopakis, Emmanuel; Pfaar, Oliver; Price, David (Rhinology, 2019)
The 2nd Rhinology Future Debate, organized by EUFOREA (European Forum for Research and Education in Allergy and Airways diseases) was held in Brussels in December 2017. One of these debates addressed the position of MP-AzeFlu in allergic rhinitis (AR) treatment. The current article summarizes this debate; reviewing recent data, and exploring how this has been interpreted by experts and incorporated into AR management guidelines and a clinical decision support system (CDSS). The Allergic Rhinitis & its Impact on Asthma (ARIA) guideline position MP-AzeFlu firstline for the treatment of AR, and in preference to intranasal corticosteroids (INSs) during the first 2 weeks of treatment. The AR CDSS recommends MP-AzeFlu as one of the firstline treatments for patients with a visual analogue scale (VAS) score <5/10 cm, and in preference (along with INS) for those with a VAS score >= 5/10 cm. Panellists agreed that AR management should be kept as simple as possible, with some preferring a 'one treatment fits all approach', while others preferred a step-up approach. The need to change the AR management mentality was acknowledged, accepting that most patients use their medication as needed and use multiple treatments; AR medications are needed which have a very fast onset of action and which target breakthrough symptoms. Panellists agreed that MP-AzeFlu has a role to play here, since it has a 5 minute onset-of-action, provides clinically-relevant symptom relief in 15 mins and AR control in < 3 days, targets nasal hyper-reactivity (NHR) which likely contributes to uncontrolled AR and breakthrough symptoms, and provides more effective AR symptom relief than INS monotherapy or INS + oral antihistamine. Finally, experts considered it likely that MP-AzeFlu should have a greater impact on asthma control than INS in co-morbid patients, but clinical data is required to back up existing pharmacoeconomic evidence. The next Rhinology Future Debate will be in held in Brussels in Dec 2019.
Gesehen am 25.06.2019